Additive manufacturing of steel–copper functionally graded material with ultrahigh bonding strength. (10th May 2021) - Tan, Chaolin; Chew, Youxiang; Bi, Guijun; Wang, Di; Ma, Wenyou; Yang, Yongqiang; Zhou, Kesong
Abstract: Additive manufacturing enables processing of functionally graded materials (FGMs) with flexible spatial design and high bonding strength. A steel-copper FGM with high interfacial strength was developed using laser powder bed fusion (LPBF). The effect of laser process parameters on interfacial defects was evaluated by X-ray tomography, which indicates a low porosity level of 0.042 % therein. Gradient/fine dendritic grains in the interface are incited by high cooling rates, which facilitates interface strengthening. Multiple mechanical tests evaluate the bonding reliability of interface; and the fatigue tests further substantiate the ultrahigh bonding strength in FGMs, which is superior to traditional manufacturing methods. Mechanisms of the high interfacial bond strength were also discussed.